Hypolipidemic Effects of a Proprietary Commiphora Mukul Gum Resin Extract and Medium-Chain Triglyceride Preparation (GU-MCT810) - Cheppail Ramachandran PhD, MBA; Smitha M. Nair PhD; Karl-W. Quirrin PhD; Steven J. Melnick PhD, MD (SAGE Publishing, 2013)
The hypolipidemic effects of the poorly soluble ayurvedic resin guggul, especially the molecular targets and mechanism, have not been well investigated to date. In the present study, we have formulated a liquid product, GU-MCT810, composed of a proprietary Commiphora mukul gum resin extract and medium-chain triglyceride and investigated its hypolipidemic effects in vitro. Treatment of HepG2 cells significantly reduced low-density lipoprotein cholesterol and increased the high-density lipoprotein/low-density lipoprotein ratio. GU-MCT810 showed direct inhibition of HMG-CoA reductase activity in a dose-dependent manner and compared very well with the inhibitory effect of statins like Pravastatin and Mevastatin. The adipocyte differentiation was also inhibited by GU-MCT810 treatment. GU-MCT810 increased the AMPKα phosphorylation and AMPK kinase activity and inhibited the phosphorylated form of mTOR expression, indicating the molecular targets affected by the nutraceutical compound. The preparation also highly upregulated the expression of LXR and PPARα genes and moderately upregulated BABP and SHP genes.